Halal Industry Development in Indonesia: Opportunities and Challenges Post Covid-19 Pandemic - Christianti, Yana Dwi; Widodo, Nova Maulud; Daroji, Choirul (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Indonesia is a country where the development of the halal industry can become a sizeable potential, not only domestically but also abroad. The halal industry has played an important role in improving the economy in Indonesia. The halal industry is recorded to have contributed USD 3.8 billion to Indonesia’s Gross Domestic Product (GDP) each year. Looking at the facts on the ground, even though Indonesia is a country with the largest Muslim population in the world. However, the large Muslim population has not been able to make Indonesia a supplier country for the needs of halal commodities in the world. For this reason, this study aims to look at the Development of the Halal Industry in Indonesia regarding Opportunities and Challenges in the Post-Covid-19 Pandemic. The data collection technique for this research uses documentation and literature studies. Documentation studies, namely by downloading files on development reports of companies and businesses engaged in the halal industry on the official website of the Indonesian Central Bureau of Statistics. The problem-solving framework in this study starts from selecting the research topic and then formulating the problem to see what the problem is to be studied. Furthermore, the researcher collects the required data and performs an analysis based on the data that has been collected, and then draws conclusions based on the descriptive analysis that was carried out. Through this research, the authors hope to contribute to a portrait of the halal industry in post-pandemic Indonesia, so that they can see opportunities for development.